Potassium hydroxide (KOH) wet preparation for the laboratory diagnosis of suppurative corneal ulcer - Akter, Laila; Salam, Md. Abdus; Begum, Nurjahan; Islam, Sofikul; Rahman, Intekhab; Ahmed, Iftikhar (Ibn Sina Trust, 2010)
Background: Suppurative keratitis is a common ophthalmic condition mostly caused by fungi. Apart from fungal culture, wet preparation using 10% Potassium hydroxide (KOH) for microscopic detection of fungal elements is a rapid and accurate method of laboratory diagnosis. Purpose: This prospective and cross sectional study was undertaken in order to evaluate the diagnostic sensitivity of wet preparation microscopy using KOH for detection of fungal agents from suppurative corneal ulcer patients. Methodology: Fifty six (56) consecutive clinically suspected patients of suppurative corneal ulcer attending Rajshahi Medical College Hospital (RMCH) during the period from July, 06 to June, 07 were included. Corneal swabs were taken aseptically for detection of bacteria in gram-stained smear and culture. Conventional mechanical corneal scrapings were collected under topical anesthesia and utilized for microscopic detection of fungal agents in KOH wet preparation and fungal cultures in the department of Microbiology of Rajshahi Medical College. Results: Culture yielded microbial growths in 47(83.93%) out of 56 samples of corneal ulcer that included 24 (42.86%) pure fungal growths, 14 (25.0%) pure bacterial growths and 09 (16.07%) mixed microbial growths (both bacteria and fungi). Direct microscopical examination using 10% KOH wet preparation detected 28 fungal agents out of total 33 fungal cases (combining both pure and mixed fungal growths in culture). Diagnostic sensitivity of wet preparation microscopy was found to be 84.85% by comparing its performance to fungal culture yields, which is the ‘gold standard’ for laboratory diagnosis. Conclusion: This limited study has revealed that wet preparation can be a tentative diagnosis of fungal keratitis and can be accurately relied upon for initiating prompt anti-fungal therapy and also recommended as a cost-effective method for laboratory diagnosis especially where culture facility is not available.